Teachers’ Readiness and Supportive Environment Toward Better Research Productivity and Skills: Basis for a Policy Development on Research Program - UY, Cristeta S.; Callo, Eden C. (Future Science / FSH-PH Publications, 2023)
The main problem of the study was to develop a standard school support program to enhance the implemented basic research program at San Jose National High School. Specifically, the determine the teachers’ level of readiness in research, the extent do the School Factors affect the teachers’ participation in research, the extent is the perceived supportive environment affect the level of research competency of teachers, Level of Competency of teachers in conducting research, the perceived level of Research Writing skills of the teachers. It identified the relationship between the teachers’ level of competency in research and the perceived level of the teachers’ readiness to conduct research and the effect of school factors, the relationship between the extent of school factors affecting participation in the conduct of research and challenges in conducting research, level of research productivity, and level of research skills and whether the perceived level of supportive environment significantly mediate the relationship between teacher’s level of readiness and the level of research productivity and level of research skills. The study was descriptive with a researcher-made questionnaire as the instrument of the study. The questionnaire was administered to 661 teachers in the Division of San Pablo City for school year 2022-2023. The data collected were treated using mean scores, standard deviation, Pearson product moment correlation, simple regression, and multiple regression analysis. Results show following findings: the teachers are all well equipped with the desired readiness needed to conduct research studies; school-related factors are very important in influencing teachers' engagement in research investigations; teacher's ability to do research projects is greatly influenced by their cognitive ability, the school's support and assistance, the principal's leadership skills, and the research culture at their institution; the teachers were all well-versed in each of the parts of a research paper; the teachers’ research skills is significantly related to the teachers’ readiness to conduct research and the effect of school factors; the relationship between effect of school factors in research engagement and challenges in conducting research is significant as well as with research productivity and research skills; and the supportive environment significantly mediate the relationship between the teachers’ level of research readiness and level of teachers’ research skills but does not significantly mediate the teachers’ level of research readiness and level of their research productivity. Strategic planning and support from the school through the developed standard school support program is encouraged.